2007
DOI: 10.1021/ja070514z
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Raman Spectroscopy for DNA Detection by Nanoparticle Assembly onto Smooth Metal Films

Abstract: A simple, sensitive, and reproducible sensing technique is described for the unambiguous detection of unlabeled single-stranded DNA by surface-enhanced Raman spectroscopy (SERS). By self-assembling probe-tethered Ag nanoparticles to a moderately smooth Ag film using the complementary target species, electromagnetic “hot spots” are created which strongly enhance the Raman signal of the species present in the hot spot. These species can include a Raman label (a molecule with a very large Raman cross-section) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
253
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 309 publications
(260 citation statements)
references
References 13 publications
5
253
0
Order By: Relevance
“…Over 5000 research articles, 100 review articles, and several books on SERS have appeared in the literature. Such a large research database provides ample testimony of the impact of SERS on both fundamental and applied studies in fields as diverse as chemistry, physics, materials science, surface science, nanoscience, and the life sciences (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Over 5000 research articles, 100 review articles, and several books on SERS have appeared in the literature. Such a large research database provides ample testimony of the impact of SERS on both fundamental and applied studies in fields as diverse as chemistry, physics, materials science, surface science, nanoscience, and the life sciences (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…The technique was used to detect two common probe molecules, R6G and 4-aminothiophenol (4-ATP) at the single molecule level. In another study, Braun et al demonstrated a single molecule SERS sensing technique for the detection of RNA and DNA, in which AgNP were assembled on an Ag film via the complementary target DNA strand, creating a strongly enhanced Raman signal [61]. Over the last decade, there has been considerable interest in SERS single molecule detection of biomolecules such as hemoglobin, glucose, cancer genes, pathogens, biological toxins and viruses [62][63][64][65][66].…”
Section: Sers For Single Molecule Detectionmentioning
confidence: 99%
“…A substantial amount of research has been carried out for the synthesis of Ag nanostructures owing to their wide and potential applications in antibacterial, antimicrobial, SERS and so forth (Wijaya et al, 2009;Braun et al, 2007;Gupta and Silver, 1998;Schultz et al, 2000). The antibacterial activity of Ag nanostructures has been studied and well documented in the literature.…”
Section: Introductionmentioning
confidence: 99%